Artificial intelligence techniques applications in the wastewater: A comprehensive review - Zakur Yahya; Márquez Fausto; Al-Taie Ali; Alsaidi Saif; Alsadoon Abeer; Mirashrafi Seyed Bagher; Flaih Laith; Zakoor Yousif (E3S Web of Conferences)
There are some challenges are firms the wastewater treatment, numerous hurdles concerning the enhancement of the energy efficiency, compliance with the increasingly stringent water quality regulations, and the maximizing resource recovery opportunities. In recent years, the computational models have garnered acknowledgment as potent instruments for tackling these various challenges, bolstering of the operational and economic effectiveness of the various wastewater treatment plants (“WWTPs”). Also, the review discusses the application of the various (AI) algorithms on the various wastewater treatment plants (WWTPs), predicting (“WWTP”) effluent properties, the wastewater inflows, the anomaly detecting, and the energy optimization. The critical gaps and the future directions in the (AI) algorithms for the wastewater treatment, including the explain ability of the data-driven models or transfer Learning processes and reinforcement learning, are also addressed.